Perspectives on the Risk-Stratified Treatment of Multiple Myeloma - Davies, Faith E.; Pawlyn, Charlotte; Usmani, Saad Z.; San-Miguel, Jesus F.; Einsele, Hermann; Boyle, Eileen M.; Corre, Jill; Auclair, Daniel; Cho, Hearn Jay; Lonial, Sagar; Sonneveld, Pieter; Stewart, A. Keith; et al. (Blood Cancer Discovery, 2022)
The multiple myeloma treatment landscape has changed dramatically. This change, paralleled by an increase in scientific knowledge, has resulted in significant improvement in survival. However, heterogeneity remains in clinical outcomes, with a proportion of patients not benefiting from current approaches and continuing to have a poor prognosis. A significant proportion of the variability in outcome can be predicted on the basis of clinical and biochemical parameters and tumor-acquired genetic variants, allowing for risk stratification and a more personalized approach to therapy. This article discusses the principles that can enable the rational and effective development of therapeutic approaches for high-risk multiple myeloma.
CRIS-Team Scopus Importer:2023-03-23